A153 EPITHELIAL-INTRINSIC INFLAMMASOME SIGNALING REVEALED USING SALMONELLA ENTERICA SEROVAR TYPHIMURIUM INFECTION OF ENTEROID DERIVED MONOLAYERS. (15th March 2019) - Han, X; Crowley, S M; Allaire, J M; Stahl, M; Knodler, L; Vallance, B
Abstract: Background: Inflammasomes are integral components of the innate immune system, providing host defense during enteric infections. Inflammasomes trigger a specialized form of cell death called pyroptosis and activate inflammatory cytokines including interleukin (IL)-18. While canonical inflammasomes use caspase 1 (Casp1), non-canonical inflammasomes signal through caspase 11 (Casp 11). We previously showed that both Casp1 and Casp 11 protect the intestine during in vivo infection by Salmonella enterica serovar Typhimurium. Notably, intestinal epithelial cells (IEC) are major targets of Salmonella, however to what degree IEC inflammasomes mediate this protective role remains unclear. In preliminary studies we tested the role of inflammasomes by infecting enteroids. Enteroids are three-dimensional cell culture grown from harvested intestinal stem cells, and while excellent in vitro models, infecting them requires micro-injection. To overcome this issue, we have developed a Salmonella infection model using IEC monolayers derived from enteroids, which significantly simplifies the process. Aims: With the enteroid monolayer model, we investigated IEC-intrinsic inflammasome activities during S. Typhimurium infection, seeking to define which inflammatory caspase(s) control IEC responses to infection, in terms of the mechanisms they use to restrict the growth of intracellular pathogens. Methods: Enteroid monolayers were derived from mice lacking components of inflammatory caspases, (Casp1 -/-, Casp11 -/- and Casp1/11 -/- ) as well as control C57BL/6 mice. The monolayers were then infected with S. Typhimurium. Microscopy was used to enumerate intracellular bacteria and assess cell shedding. Western Blots and ELISA were used to measure IL-18 production and secretion. Results: IEC-intrinsic inflammasomes play important roles during S. Typhimurium infection. Casp1/11 -/- monolayer cells carried the highest number of intracellular bacteria, followed by Casp1 -/-, Casp11 -/- then C57BL/6 cells. IL-18 secretion appeared to be in reverse, with highest production in C57BL/6 and lowest in Casp1/11 -/- cells. Thus caspase 1 from canonical inflammasome seems to play the major role in inducing IEC shedding and limiting the number of intracellular bacteria, while promoting IL-18 production. Caspase 11 from the non-canonical inflammasome complements Caspase 1 but has a less significant role in restricting infection. Conclusions: These results indicate that enteroid monolayers use both canonical and non-canonical inflammasomes to defend against intracellular S. Typhimurium, restricting infection through active shedding and recruiting immune cells via IL-18 production. Furthermore, enteroid monolayers are an excellent model for infection studies, and could even be applied in the future to study commensal-IEC interactions. Funding Agencies: CAG, CCC, CIHRNIH